2017
DOI: 10.1007/s00267-017-0929-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Institutional Mechanisms for Scientific Input into the Management Cycle of the National Protected Area Network of Peru: Gaps and Opportunities

Abstract: Understanding how to improve decision makers' use of scientific information across their different scales of management is a core challenge for narrowing the gap between science and conservation practice. Here, we present a study conducted in collaboration with decision makers that aims to explore the functionality of the mechanisms for scientific input within the institutional setting of the National Protected Area Network of Peru. First, we analyzed institutional mechanisms to assess the scientific informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…Our approach can be used to implement transdisciplinary processes where the scientific, public, and policymaking communities work together with the goal of developing private conservation strategies (López-Rodríguez et al 2017). Although our results refer to a specific case study in the Western U.S., the approach proposed can be easily translated to other areas in the world, because private lands are proliferating both in the developing world and in industrialized countries.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach can be used to implement transdisciplinary processes where the scientific, public, and policymaking communities work together with the goal of developing private conservation strategies (López-Rodríguez et al 2017). Although our results refer to a specific case study in the Western U.S., the approach proposed can be easily translated to other areas in the world, because private lands are proliferating both in the developing world and in industrialized countries.…”
Section: Discussionmentioning
confidence: 99%
“…Ello se podría posiblemente conseguir mediante algún tipo de institucionalización, pero será importante mantener la flexibilidad y capacidad adaptativa necesaria para poder responder a las necesidades futuras de las diferentes categorías de actores representadas. Además, será importante desarrollar los mecanismos necesarios para facilitar la contribución efectiva del conocimiento científico a la práctica y política de la conservación de la biodiversidad (López-Rodríguez et al 2017). De hecho, de según Cvitanovic y Hobday (2018) sobre la base del análisis de casos de implementación exitosa, los pasos necesarios después de la constitución de una interfaz CGS incluyen la realización de proyectos de investigación participativos, la implementación de un sistema de manejo de conocimientos diseñado a la medida, y el asegurar una colaboración continua que incluya un contacto regular cara a cara y un proceso de reflexión y aprendizaje conjuntos.…”
Section: Discussionunclassified
“…In addition to promoting knowledge transfer amongst the participants, we observed that this shared leadership led to a balanced representation of both countries and strengthened relationships between the participants from the bordering countries. Considering that knowledge-brokering approaches can be adapted based on the context, actors and desired goals (see, e.g., [67,70]), our results suggested that a shared approach between brokers of different countries can be a key factor for facilitating knowledge exchange and building confidence in cross-border contexts. Second, the development of a clearly structured, systematised and timed learning process focused the collective deliberations on specific areas [71].…”
mentioning
confidence: 90%